Arnold O. Beckman and William Ballhaus (1967)
Dr. Arnold O. Beckman (1900-2004) invented the first commercially successful electric pH meter in 1934 and thus began a long career manufacturing scientific and medical instruments with National Technical Laboratories, Arnold O. Beckman, Inc., and Beckman Instruments. After his retirement he devoted his life to philanthropy and specifically supporting scientific innovation. Dr. William F. Ballhaus, Sr. (1918-2013) was a Stanford- and Caltech-educated aeronautical engineer who assumed the presidency of Beckman Instruments in 1965. During his tenure, Ballhaus oversaw the company's shift away from space and defense applications in favor of medical instrumentation. He served as vice chairman and chief executive officer following Beckman's acquisition by Smith Kline, retiring in 1983. This image, with Beckman seated behind the desk, shows the two men reviewing company operations for fiscal year 1967.
Keywords: Scientists--Portraits; Beckman, Arnold O.; Ballhaus, William F., 1918-; Chief executive officers; Beckman Instruments, Inc.